Does a Hand Strength–Focused Exercise Program Improve Grip Strength in Older Patients With Wrist Fractures Managed Nonoperatively?: A Randomized Controlled Trial. (April 2020) - Nguyen, Antony; Vather, Mehr; Bal, Gobind; Meaney, Donna; White, Megan; Kwa, Myles; Sungaran, Jai
Abstract : Objective: Distal radius fractures in the older population significantly impair grip strength. The aim of the study was to investigate whether a hand strength focused exercise program during the period of immobilization for nonoperatively managed distal radius fractures in this population improved grip strength and quality of life. Design: This is a single-center randomized controlled trial with concealed allocation, assessor blinding, and intention-to-treat analysis. Fifty-two patients older than 60 yrs who experienced distal radius fractures managed nonoperatively with cast immobilization. The intervention group ( n = 26) received a home hand strength–focused exercise program from 2 and 6 wks after injury while immobilized in a full short arm cast. The control group ( n = 26) performed finger range of motion exercises as per protocol. Primary outcome was grip strength ratio of injured arm compared with uninjured arm. Secondary outcome included functional scores of the 11-item shortened version of the Disabilities of the Arm, Shoulder and Hand. Outcomes were measured at 2, 6, and 12 wks after injury. Results: The intervention group significantly improved grip strength ratio at both 6 and 12 wks (6 wks: 40% vs 25%, P = 0.0044, and 12 wks: 81% vs 51%, P = 0.0035). The intervention group improved the 11-item Disabilities of the Arm, Shoulder and Hand score at 12 wks; however, this was not statistically significant (25 vs 40, P = 0.066). Conclusions: A hand strength–focused exercise program for elderly patients with distal radius fractures while immobilized significantly improved grip strength. Abstract : Supplemental digital content is available in the text.